FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Salsabiela, Adinda Shafira; Sufiyati, Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this research is to obtain empirical evidence about the effects of firm size, profitability, leverage, sales growth, and capital intensity ratio on tax avoidance of the manufacturing companies listed on the Indonesia Stock Exchange during 2018-2020. The data used are secondary data taken from financial reports in which 80 companies meet the sampling criterias. Samples processing techniques are obtained through purposive sampling method and the data were analyzed by using multiple linear regression analysis what helped by Eviews version 12. The result of the research indicates that leverage and sales growth have a significant influence on tax avoidance. However firm size, profitability, and capital intensity ratio have no significant influence on tax avoidance. The implication of the research is to increase comprehension for companies to be wiser in making decisions to do tax avoidance practices and become an evaluation for the government to determine the right policy to resolve tax avoidance practices.